“No, Gender doesn’t make a Difference…?” Studying Negotiations and Gender in Organizations - Bloksgaard, Lotte (Qualitative Studies, 2012)
This article focuses on methodological challenges and strategies with regard to studying gender in organizations. Work organizations are often thought, theorized and talked about as gender-neutral arenas and, therefore, gender is often seen as irrelevant and of no importance in modern work-life. There is also often a discrepancy in relation to gender between discourse and practice, which makes it difficult to capture the significance of gender in organizations by the interview method alone. On the basis of two empirical studies, focusing on the significance of gender in negotiations of wage and parental leave in the work place, the article explores some of the challenges and complexities involved when researching gender as a social category of difference, which produces inequalities in organizations. Furthermore, the article demonstrates and discusses how applying and combining different methods and research strategies – for example following specific negotiations to a conclusion - provide insight into the production of gender in discourse and practice at the work place level. Thus, the article argues that reflexivity and methodological plurality are important when studying gender in work organizations.